Feed digestibility and productive performance of bullfrogs fed in high and low frequency - de Castro, Cecilia Silva [UNESP]; Agostinho, Claudio Angelo; Argentim, Daniel [UNESP]; de Alexandre, Juliana Sversut; de Oliveira, Luciano Caetano; Ramalho de Sousa, Rodrigo Morgado; Padilha, Pedro de Magalhaes [UNESP] (Elsevier B.V., 2012)
This study evaluated the effect of the feeding frequency on growth performance of bullfrogs (Lithobates catesbeianus) and established the coefficients of availability of calcium and phosphorus and the coefficient of digestibility of the protein in the feed. Three feeding frequencies (6, 24 and 46 meals per day) were tested in a completely randomized design with four replications. Bullfrogs with an average weight of 70.59 +/- 1.05 g were selected and divided into 12 growth pens located inside a greenhouse. Automatic feeders supplied the feed. Silica (SiO2) was used as an internal marker for the determination of protein digestibility and the availability of calciumand phosphorus. The best growth was observed in animals fed with 46meals per day (meals d(-1)). At the end of the experiment, the frequencies of 6, 24, and 46 meals d(-1) provided feed conversion rates of 2.31, 1.88 and 1.20, respectively. The different feeding frequencies did not influence the apparent digestibility of protein and apparent availability of calciumand phosphorus in the feed supplied to the bullfrogs. It is recommended to provide feed to bullfrogs at a frequency of 46 meals d(-1). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Automatic feeding; Feed management; Growth; Lithobates catesbeianus; Wet system